Taxonomic reassessment of Hypericum austroyunnanicum (Hypericaceae) supports its synonymy with H. wightianum - Bai, Rui-Zhu; Yu, Jia-Xin; Xiang, Chun-Lei (Phytotaxa, 2026)
Based on a comprehensive examination of herbarium specimens, field investigations, and phylogenetic analyses, we demonstrate that Hypericum austroyunnanicum , previously reported from Menglian county, Yunnan province, China, is conspecific with H. wightianum. According, H. austroyunnanicum is here reduced to synonymy under H. wightianum. A morphological description and photographic illustrations of H. wightianum are provided.